Analysis proximate of sargassum seaweed sp. Issue 1 (July 2021) - Winarni, S; Zainuri, M; Endrawati, H; Arifan, F; Setyawan, A; Wangi, A P
Abstract: Sargassum sp. seaweed becomes one of the interesting food preparations for the community and can be a potential local food-based product because this type of brown seaweed can be processed into food, pharmaceutical, cosmetic, and textile products. Seaweed Sargassum sp. has economic value and protection for marine life. Sargassum sp can be beneficial in the health field because it contains protein, minerals, alginates, active compounds of steroids, alkaloids, and phenols that function as antibacterial, antifungal, and antiviral properties. Sargassum sp., was the largest class of brown algae (Phaeophyta) in tropical seas. The purpose of this study was to determine the nutritional composition of Sargassum sp. which includes protein content, fat content, ash content, and water content. The method used is a proximate analysis method based on SNI 01-2354.4-2006, SNI 2891 01 1992, SNI 01-2354.1-2006, and SNI 2354.2: 2015. The results obtained were Sargassum sp protein levels of 3.048% higher than E. cottonii. Fat content in Sargassum sp of 0.617% of dry weight is lower than E. cottonii. The ash content of Sargassum sp was 7.112% higher than that of E. cottonii in proportion to the mineral content of the two seaweeds. The water content of Sargassum sp was 67.281% lower than E. cottonii, both of which were higher than the specified water content standard of <32%. This is also influenced by the drying process. Conclusion: Sargassum sp has good content to be consumed and used as local food products.